2006
DOI: 10.1079/asc200530
|View full text |Cite
|
Sign up to set email alerts
|

Genetically modified soya bean in rabbit feeding: detection of DNA fragments and evaluation of metabolic effects by enzymatic analysis

Abstract: The presence of DNA fragments in tissues from rabbits given genetically modified (GM) soya-bean meal (solvent extracted) was investigated by using the polymerase chain reaction (PCR) approach. Moreover, the possible effects on cell metabolism were evaluated by determination of several specific enzymes in serum, heart, skeletal muscle, liver and kidney. The chloroplast sequence for tRNA Leu by using the Clor1/Clor2 primers designed on chloroplast trnL sequence was clearly detected. On the contrary, two couples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
42
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 26 publications
7
42
0
Order By: Relevance
“…In our study, the weight of the organs of kids did not differ between groups, in accordance to findings of previous research (Tudisco et al, 2006b) carried out on rabbits fed GM soybean meal.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In our study, the weight of the organs of kids did not differ between groups, in accordance to findings of previous research (Tudisco et al, 2006b) carried out on rabbits fed GM soybean meal.…”
Section: Discussionsupporting
confidence: 93%
“…A similar shift has been previously described in rabbits (LDH-H 4 . LDH-H 1 M 3 ) where the higher amount of H subunit was assumed to mean a higher specificity for the reduction of alpha-hydroxybutyrate to alpha-oxobutyrate, thereby showing that some metabolic changes occurred in the liver (Tudisco et al, 2006b). Our data confirm this hypothesis: the isoenzyme mainly composed by the H subunit showed an increased percentage, which was also found in the muscle where LDH1 is not the dominant isoenzyme.…”
Section: Enzyme Assaysupporting
confidence: 82%
See 1 more Smart Citation
“…In recent years, in certain areas of the world, particularly those where soybean is not cultivated, a trend has emerged for the elimination of extracted SBM from feed rations for most livestock. The reason reported for such a measure is the willingness to become independent from imported feed, or the fear of products containing Genetically Modified Organisms (Tudisco et al 2006). As regards the feeding of rabbits, the possibility for the substitution of soybean meal with other plant feeds containing significant amounts of proteins has been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Several data indicate liver and kidney problems as end points of GM diet effects [2]. Tudisco et al [3] hypothesised that cell metabolism of several enzymes was altered in rabbit fed GM soybean and the same authors found transgenic DNA fragments in goat milk but also in kids organs when mothers are fed GM soybean and revealed elevated levels of LDH in tissues, thus suggesting an increase in cell metabolism [4]. Aim of this paper was to investigate the presence of DNA fragments and the activity of gamma-glutamyltransferase (GGT) in blood and organs from kids whose mothers were fed GM soybean.…”
Section: Introductionmentioning
confidence: 99%